A Case Report of Modified Radical Mastectomy (MRM) In A 59-Year-Old Female Patient With Comorbid Bronchiectasis Using Thoracic Segmental Spinal Anesthesia (TSA) - Imam Ghozali; Hario Tri Hendroko; Dansen Rudyanto; Marcella Dena Fernanda (Medula, 2023)
Breast cancer is a disease with the highest incidence of malignancy in Indonesia and the world. Epidemiological studies have shown that cancer affects billions of women each year. The incidence of breast cancer increases with age. In the elderly, the possibility of co-morbidities which are comorbid major medical problems makes anesthetic management decisions more complicated and perioperative care more challenging. Increasing age and comorbidities are the most important risk factors for postoperative complications. TSA was performed on a 59-year-old female patient with comorbid bronchiectasis who received MRM. The level of needle insertion was between T5-T6, premedication in the form of 0.5 mg alprazolam tablets, initiation of TSA with 1 ml of 0.5% hyperbaric bupivacaine and 20 mcg of fentanyl. The level of sensory block achieved was between T1-T7. TSA resolved without complications. The patient remained comfortable during the operation and there was no significant change in the patient's hemodynamics, airway and breathing. There were no postoperative complications. Thoracal segmental spinal anesthesia (TSA) is a safe alternative in performing modified radical mastectomy (MRM) and other breast surgeries because it has highly selective spinal block capabilities, ensures better control during induction and surgical processes, stability of the respiratory system and cardiovascular, and reduces the need for local anesthetics and has a lower risk of toxicity.